2020
DOI: 10.1007/s10072-020-04866-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, onset, and evolution of neurological symptoms in patients with COVID-19

Abstract: Background A wide range of neurological manifestations has been described in COVID-19. Methods In this nationwide retrospective observational study, patients in Tunisia diagnosed with COVID-19 between the 2nd of March and the 16th of May 2020 were contacted by telephone. We collected demographic and clinical data and specified characteristics and evolution of main neurological symptoms. Results Of 1034 confirmed COVID-19 patients, 646 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
(49 reference statements)
3
26
1
2
Order By: Relevance
“…In previous studies on the neurological aspects of COVID-19, the incidence of neurological manifestations (including nonspecific symptoms) has varied widely, from 36% to 72%. 2 11 12 13 14 Similar to the present findings, the most common symptoms reported previously were headache, myalgia, smell and taste impairment, and impaired consciousness. A recent systematic review found that the symptoms of headache, dizziness, smell dysfunction, and impaired consciousness occurred in 20.1, 6.8, 59.2, and 5.1% of patients, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In previous studies on the neurological aspects of COVID-19, the incidence of neurological manifestations (including nonspecific symptoms) has varied widely, from 36% to 72%. 2 11 12 13 14 Similar to the present findings, the most common symptoms reported previously were headache, myalgia, smell and taste impairment, and impaired consciousness. A recent systematic review found that the symptoms of headache, dizziness, smell dysfunction, and impaired consciousness occurred in 20.1, 6.8, 59.2, and 5.1% of patients, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…A study from Wuhan found that some patients with COVID-19 had neurological symptoms as their presenting manifestations, 2 and one observational study found that neurological symptoms preceded respiratory symptoms in 14.5% of patients with COVID-19 and were the only symptoms of the disease in 22.7%. 12 In another observational study investigating the initial symptoms of COVID-19, neurological symptoms were found in 9.7% of the patients. 48 In another study, the onset of anosmia was noted early in 73% of the patients prior to the diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Anosmia and ageusia are common symptoms of COVID-19 [36], and the olfactory epithelium are some of the earliest cell types to be infected [37]. Theoretically, if the virus can pass to olfactory sensory neurons, it could travel across the cribriform plate to arrive at the olfactory bulb, and subsequently access other brain regions [34].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no definitive evidence supporting the contribution of direct neuronal infection to the development of encephalopathy, delirium, and other neurological manifestations observed in patients with COVID-19 [ 12 ]. In Northern Africa, neurological manifestations of COVID-19 have been reported in several hospital-based cross-sectional studies [ 13 - 15 ]. On the contrary, apart from a few case reports [ 16 - 18 ], data on the neurological manifestations of COVID-19 in sub-Saharan Africa are scarce.…”
Section: Introductionmentioning
confidence: 99%